Air pollution - selected health effects in Poland - Zieliński, Ewa; Wielgus, Adriana; Dreliszak, Jakub; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Air quality in Poland for many years is one of the lowest in the European Union, while the level of pollution is many times higher than the standards set by the World Health Organization (WHO). As a consequence, it has a negative effect on the human body. The article shows the problem of air pollution and the health effects of harmful factors emitted to the atmosphere.